1981
DOI: 10.1002/jcp.1041080317
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the prereplicative changes in the synthesis and transport of messenger and ribosomal RNA in regenerating livers of normal and hypocalcemic rats

Abstract: Partial hepatectomy induces increases in the synthesis of both messenger (poly(A)+) and ribosomal (poly(A)-) RNA, which precede the initiation of DNA synthesis. The increase in poly(A)+RNA, which commences soon after surgery and reaches a peak 1-3 hours later is particularly striking. Disruption of this early increase in poly(A)+RNA synthesis by colchicine (and other microtubule disrupters) or indomethacin results in a failure to initiate DNA synthesis. This suggests that prostaglandins and the microtubules ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…Using hybridization studies with [3H]-poly(U), we have observed that there is approximately a 25% increase in poly(A)+ containing RNA by 24 hr after unilateral nephrectomy (data not shown). This result is consistent with the reported increases in poly(A)+ mRNA following partial hepatectomy (Atryzek and Fausto, 1979;Glazer, 1976;Walker and Whitfield, 1981) and in mammalian cells stimulated to grow in vitro Johnson et al, 1974). The rapid accumulation of poly(A)+ RNA during the transition from the resting to the growing state may represent an increased efficiency of HnRNA transcription and conversion into cytoplasmic poly(A)+ mRNA (Atryzek and Fausto, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…Using hybridization studies with [3H]-poly(U), we have observed that there is approximately a 25% increase in poly(A)+ containing RNA by 24 hr after unilateral nephrectomy (data not shown). This result is consistent with the reported increases in poly(A)+ mRNA following partial hepatectomy (Atryzek and Fausto, 1979;Glazer, 1976;Walker and Whitfield, 1981) and in mammalian cells stimulated to grow in vitro Johnson et al, 1974). The rapid accumulation of poly(A)+ RNA during the transition from the resting to the growing state may represent an increased efficiency of HnRNA transcription and conversion into cytoplasmic poly(A)+ mRNA (Atryzek and Fausto, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…The total RNA concentrations both in the nucleus and in the cytoplasm (including cytoplasmic poly A + mRNA) reached to a maximum level within 24 hrs of RH., but their level decreased sharply within 48 hrs of RH. Whereas the nuclear poly A § mRNA level remained unaltered during this period [37,38]. Though, there was no remarkable change in liver specific mRNA transcription rate or its concentration within first 24 hrs of RH.…”
Section: Discussionmentioning
confidence: 77%
“…The process leading to DNA synthesis is inhibited by indomethacin, but is not mediated by products of arachidonic acid metabolism, while the mitosis-determining process is inhibited by mefenamic acid and gluwcorticoids and mediated by prostaglandins or thromboxane. Although the nature of these separate processes are completely unknown, the mitosis-determining event in liver cells coincides with a transient surge of messenger RNA, which also peaks 2 to 3 hours after partial hepatectomy and is inhibited by indomethacin (Walker and Whitfield, 1981). Whether or not this surge of messenger RNA is related to the mitosisdetermining process or the events leading to DNA synthesis, or both, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%